2022
DOI: 10.1021/acs.iecr.1c05035
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanism Underlying Wetting Behavior of the Vacuum Membrane Distillation during Desalination

Abstract: Membrane wetting is a crucial issue in the desalination process by vacuum membrane distillation (VMD). However, the micromechanism of the wetting behavior is far from clear. Here, electrospun nanofiber membranes (ENMs) had been utilized to clarify the pore variations inside the membrane for desalination from NaCl aqueous solution, where the distinct open pore structure of ENMs could address the characterizing limitations for the change occurring in the membrane pores. A wetting formation model had been depicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Also, in the terminal of the tests, no scale layer was observed with the SEM technique, and only a few crystal particles were found (Figure 2g1). This result was also reported in a previous study, 23 that no NaCl scale layer was observed in terminal SEM images of the membrane. We also tested other highly soluble salts, including KCl and Na 2 SO 4 , and a poly(tetrafluoroethylene) (PTFE) membrane in MD (Figure S3).…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Also, in the terminal of the tests, no scale layer was observed with the SEM technique, and only a few crystal particles were found (Figure 2g1). This result was also reported in a previous study, 23 that no NaCl scale layer was observed in terminal SEM images of the membrane. We also tested other highly soluble salts, including KCl and Na 2 SO 4 , and a poly(tetrafluoroethylene) (PTFE) membrane in MD (Figure S3).…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…Also, in the terminal of the tests, no scale layer was observed with the SEM technique, and only a few crystal particles were found (Figure g1). This result was also reported in a previous study, that no NaCl scale layer was observed in terminal SEM images of the membrane.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…28−31 MD has similar advantages to membrane absorption but is more efficient in bromine extraction by imposing extra vacuum forces. 32,33 The hydrophobicity of the membrane prevents the infiltration of the aqueous solution, because only vapor can be transported through the pore channels, so MD can theoretically achieve a nearly complete rejection of nonvolatile salts. 34,35 Tang et al 36 employed a membrane distillation process to separate bromine−water mixtures with different flat polyurethane membranes.…”
Section: Introductionmentioning
confidence: 99%